Large, but short-term, increase in fecal indicator bacteria following extreme flooding from Hurricane Harvey in Houston, TX - Mukherjee, Maitreyee; Hossain, Md Shakhawat; Boswell, John; Zhang, Yan; Allen, Michael S.; LaMontagne, Michael G.; Gentry, Terry J. (Frontiers in Water, 2024)
Hurricane Harvey caused widespread flooding along the Texas Gulf Coast in August 2017; some areas of Houston received >150 cm of rainfall within a few days. Due to concerns over fecal contamination of floodwaters, surface water samples were collected at six locations in the southeastern Houston area immediately before and after the hurricane and then every 1 to 2 weeks thereafter over a 2-month period. Total E. coli was enumerated using the IDEXX Quanti-Tray/2000 system. DNA extracted from water samples was analyzed via quantitative real-time PCR (qPCR) for general and source-specific total Bacteroidales and human Bacteroidales markers, and digital PCR (dPCR) for antibiotic resistance genes (ARG) and a plasmid (pBI143) associated with human waste. SourceTracker2 was used to determine human source contributions based on metagenomic analysis of PCR-amplified 16S rRNA gene fragments. Samples collected immediately after the hurricane had elevated levels of E. coli, ranging from 488 to 1,733 CFU 100 ml−1. After 1 week, E. coli levels decreased to <100 MPN 100 ml−1. Total Bacteroidales numbers were elevated immediately following the hurricane and remained high for 12 days. Human-source contributions, as assessed by PCR methods and metagenomic analysis, peaked within 12 days after the hurricane consistently across all sampling sites. Multiple regression analysis of environmental parameters, copies of ARG and pBI143, and metagenomic data confirmed that human waste caused the dramatic, short-term, high levels of fecal contamination of floodwaters generated by Hurricane Harvey. Fecal indicators approached normal background levels approximately 3 weeks after the rainfall ended.